B2C arbitration : - Bellohlávek, Alexander J. (JurisNet, LLC, 2012)
The controversial variable is the degree of protection to be afforded to the consumer, both under the applicable substantive law and in procedural terms. These are the main issues addressed in this book. Apart from the key topic, the author has extensively elaborated on certain fundamental categories such as public interest and public policy (all primarily in connection to the procedural mechanisms of consumer protection); he has also analyzed the applicable European law and the case law of the ECJ and offered an overview of the individual systems employed in both European and non-European countries (especially the USA and Canada).